A Review of Maqāshid Sharīa on Handling the COVID-19 Pandemic in Lampung and West Java Province - faisal, faisal; Mu'in, Fathul; Edi, Relit Nur; Santoso, Rudi (Universitas Islam Negeri Raden Intan Lampung, 2024)
This research aims to determine and analyze the handling of the COVID-19 pandemic in Lampung Province and West Java from the perspective of maqāshid sharīa. Given that the pandemic has a wide impact on society, its handling must be comprehensive. This research method uses a qualitative method with an ethnographic approach. The data was obtained from the Lampung and West Java Provincial Governments, namely from the Regional Secretary and members of the DPRD. The data analysis uses interactive analysis and concept analysis. This study found that to handle the COVID-19 pandemic, the Lampung and West Java Provincial Governments have made several policies, including regional and gubernatorial regulations. The policy is intended to limit the worship and economic activities of the community. From the perspective of maqāshid sharia, restrictions on worship and economic activities are part of protecting the human soul (hifdz al-nafs) as the highest protection or value before wealth (hifdz al-māl) and even religion (hifdz al-dīn). With this handling, the rate of the virus spread can be prevented so that more human lives can be saved